Implementation of Project-Based IPAS Learning Integrated With Pancasila Student Profile to Enhance Creativity and Social Care of Fifth-Grade Students at SDN 237 Pinrang - Nuryati Nuryati; Yunus Busa; Asbar Asbar (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to analyze the implementation of project-based Integrated Natural and Social Sciences (IPAS) learning integrated with Pancasila Student Profile in enhancing creativity and social care among fifth-grade students at SDN 237 Pinrang. The research method employed was classroom action research with qualitative and quantitative approaches conducted in two cycles. The research subjects were 28 fifth-grade students at SDN 237 Pinrang. Data collection techniques included observation, creativity tests, social care questionnaires, interviews, and documentation. Data analysis was conducted descriptively using both qualitative and quantitative methods with descriptive statistics. The results demonstrated that the implementation of project-based IPAS learning integrated with Pancasila Student Profile effectively enhanced student creativity from an average of 68.5 in cycle I to 84.2 in cycle II. Student social care also increased from moderate category 67.3% to high category 89.7%. The implementation involved projects relevant to daily life such as waste management, water conservation, and local wisdom of Pinrang that integrated elements of Pancasila Student Profile. The research concludes that project-based IPAS learning integrated with Pancasila Student Profile is effective in enhancing student creativity and social care through meaningful and contextual learning experiences.